The beak that grips: maternal indifference, ambivalence and the abject in The Babadook. Issue 1 (2nd January 2017) - Buerger, Shelley
ABSTRACT: This article investigates the depiction of maternal indifference and ambivalence in Jennifer Kent's film The Babadook . Using the techniques of psychoanalytical criticism I draw on Kristeva's [1982. Powers of Horror: An Essay on Abjection . Translated by Leon S. Roudiez. New York: Columbia University Press] theory of abjection and Barbara Creed's [1993. The Monstrous Feminine: Film, Feminism, Psychoanalysis . London: Routledge] application of this to the horror genre to explore the film's portrayal of repressed grief and the resulting traumatic disruption to the mother/child bond. Taking the protagonist's troubled relationship with both her son and her bereaved status as my starting point, I argue that The Babadook represents a reimagining of maternal abjection. Both Kristeva and Creed posit that abjection is first experienced as the result of the mother's refusal to relinquish her hold on the child and to move past the intense dyadic relationship of the infant period. The Babadook inverts this psychic narrative by positioning Amelia's refusal of this relationship and her lack of proper maternal feeling as the site of her abjection. In this reimagining of maternal abjection, The Babadook presents audiences with a representation of maternal experience that is shocking and confronting. While the narrative arc is ultimately one of redemption the ambiguous ending emphasises the lingering unease inspired by maternal indifference.